Can the Side Effects of Mydriatics Be Reduced with the ROP-bundle Protocol? - Özlem ŞAHİN; Özmert M.A. ÖZDEMİR; Ebru Nevin ÇETİN; Kazım KÜÇÜKTAŞÇI; Hacer ERGİN (Namık Kemal Tıp Dergisi, 2023)

(untitled)
Aim:The mydriatics that used for pupil-dilation in the examination of retinopathy-of-prematurity (ROP) may cause some side-effects in the neurological, gastrointestinal, cardiovascular systems by absorption from the nasal mucosa, cornea, conjunctiva, skin. In order to minimize these side-effects, it’s recommended to prepare mydriatics in appropriate concentrations, combinations, and to apply pressure on the naso-lacrimal canal by closing the eyes after the application. In this study, we aimed to evaluate the systemic side-effects in the early period of using 0.5% cyclopentolate-1% phenylephrine combination for pupil-dilatation before the ROP-examination and with the protocol we applied after drip in our unit.Materials and Methods:Thirty-three ROP examinations of 17 cases were included in the study, which was planned retrospectively. After instillation of eye drops containing 0.5% cyclopentolate-1% phenylephrine combination in accordance with our ROP-bundle-protocol, the eye was closed, pressure was applied to the naso-lacrimal canal for 1-2 minutes, and the excess part that had leaked into the skin was wiped off. Oxygen saturation (SaO2), the amount of oxygen given, blood pressure arterial (TA), heart rate were recorded before and after the drop at 10., 30., and 60. minutes. In addition, patients were followed up for 24 hours in dimensions of gastric-residue, distention, apnea and other side-effects.Results:The mean-week of gestation, body weight of 17 newborns, 35.3% (6) of whom were boys, 64.7% (11) of girls, were found to be 27.6±3 weeks, 1025±389 g, respectively. In 33 evaluations made before and after mydriatic in 17 cases; distension developed in two cases, apnea in one, and pallor of the skin in one patient. Although there was a statistically significant difference only in SaO2 and 60th minute systolic TA-measurements between pre- and post-treatment measurements, hemodynamic changes were not evaluated as clinically significant.Conclusion:In-order-to reduce the side-effects that may develop due to mydriatics, it’s necessary to standardize the practices before and after the ROP-examination, close follow-up of the cases after the ROP-examination in terms of early intervention.